The most significant methods of mastering of communicative competence in target language (Texas Journal of Engineering and Technology, 2022)
Higher education plays an important role in developing communicative skills of ESP learners. ESP is oriented towards mastering the skills for professional communication. However, most of the students find themselves incompetent in the course of their work. The article discusses the benefits of using a project work to history students to improve their speaking skills as well as professional communication. The topicality of the article is determined by the fact that the projects proposed have not been actively introduced into curriculum designed for history students. The article is aimed at analyzing the problems the teachers face in teaching process. It proposes six methods for teachers as practical advice that can be used effectively to master students’ speaking skills at the end of the project. The results show that implementing project is very effective in improving speaking, critical thinking skills, creativity, and how to manage the time. The purpose of the article is to encourage ESP students to learn English through introducing new approaches to teaching. The author indicates that apply project work to language learning raises the academic achievement in which students explore the real world challenges